2011
DOI: 10.1021/ac200591a
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fiber-Optic Attenuated Total Reflection-FT-IR Methods for In Situ Characterization of Protein Delivery Systems in Real Time

Abstract: Real Time Characterization of Protein Delivery Systems A fiber optic coupled ATR-FTIR spectroscopy technique was applied to the study of two different therapeutic delivery systems, acid degradable hydrogels and nanoparticles. Real time exponential release of a model protein, human serum albumin (HSA), was observed from two different polymeric hydrogels formulated with a pH sensitive crosslinker. Spectroscopic examination of nanoparticles formulated with an acid degradable polymer shell and encapsulated HSA exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Further, as SPIONs are of a similar size to proteins (10 nm), the measured release kinetics are likely proportional to those for proteins; we have previously shown that polyketal nanoparticles allow rapid release of protein cargo. 10 While a few methods exist for real-time measurement of nanoparticle release kinetics, 37,38 release is often measured by taking aliquots over time and isolating released drug or protein, 5,39−45 usually through centrifugation. 20 However, because of their small particles may not be completely separated from the released cargo; long centrifugation may also change the time interval over which release is determined.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Further, as SPIONs are of a similar size to proteins (10 nm), the measured release kinetics are likely proportional to those for proteins; we have previously shown that polyketal nanoparticles allow rapid release of protein cargo. 10 While a few methods exist for real-time measurement of nanoparticle release kinetics, 37,38 release is often measured by taking aliquots over time and isolating released drug or protein, 5,39−45 usually through centrifugation. 20 However, because of their small particles may not be completely separated from the released cargo; long centrifugation may also change the time interval over which release is determined.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Direct evaluation of delivery kinetics represents a challenge as it requires sensitive methods capable of differentiating between encapsulated and released materials [1217]. One of the most common approach to this challenge is to encapsulate solvatochromic fluorophores, whose emission spectra vary depending on the polarity of their environment [18], and measure a steady-state decrease in fluorescent intensity and/or a positive solvatochromic shift in the emission spectrum as they are released into an aqueous environment [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the binding of proteins and other ligands on flat surfaces, and their associated conformational changes, have been thoroughly investigated using a wide range of methods, [24][25][26][27][28][29][30][31][32][33] including attenuated total reflectance (ATR) based spectroscopies, atomic force microscopy, circular dichroism (CD), surface enhanced Raman spectroscopy (SERS), quartz crystal microbalance (QCM), and ellipsometry, among others. Some of these techniques have also found application in the study of ligand-NP interactions, in particular CD, 34,35 SERS, 36,37 QCM, 38 ATR-Fourier transform infrared (FTIR) 21,39,40 spectroscopy and ATR-fluorescence spectroscopy. 41 Beyond these, a wide range of both traditional and novel methods have been used to probe the interaction between NPs and various ligands, both qualitatively and quantitatively.…”
Section: Introductionmentioning
confidence: 99%